Moral psychology : historical and contemporary readings - Nadelhoffer, Thomas; Nahmias, Eddy A., 1969-; Nichols, Shaun (Malden, MA : Wiley-Blackwell, 2010)
'The tremendous growth of scientific research on emotion, decision-making, moral judgment, and moral behavior in recent years has given rise to a rich literature of scientifically-informed philosophical work on moral psychology. This volume is the first book to bring this literature together with the most significant foundational works from philosophy and psychology. Approaching moral psychology from an empirically informed perspective, this collection shows the deep continuity between historical discussions in philosophical ethics and contemporary work in empirically oriented moral psychology. The selections explore a wide range of topics from passion and altruism to virtue and responsibility, with editorial material providing context and highlighting the connections running between the pieces. Including historical selections from philosophy, classic pieces from 20th-century psychology, and some of the most significant contemporary contributions from philosophers, psychologists, and other cognitive scientists, Moral Psychology: Historical and Contemporary Readings provides a comprehensive introduction to this important field'--
Includes bibliographical references (p. [388]-390).
Keywords: Ethics; Moral development; Psychology -- Moral and ethical aspects; Psychology and philosophy